2016
DOI: 10.3892/etm.2016.3319
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinases and tissue inhibitor of matrix metalloproteinases in the hair cycle

Abstract: According to the growth state of hair follicles, the hair cycle is divided into the anagen, catagen and telogen phases. A number of biological factors have been shown to synchronize with the hair cycle. As an important component of the hair follicle, the extracellular matrix is regulated by matrix metalloproteinases (MMPs) and their inhibitors (tissue inhibitor of matrix metalloproteinases; TIMPs). It has been reported that MMP-2, MMP-9 and TIMP-1 are associated with the hair cycle; however, their expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
(33 reference statements)
0
16
0
2
Order By: Relevance
“…We also noted that highly efficient ablation of TGFβ occurs following topical application to 6 week old mice with another peak at 10 weeks. This timing is similar to the mouse hair anagen cycle [35]. It is possible that topical tamoxifen targeting genes in KC may have heightened efficiency during anagen.…”
Section: Discussionmentioning
confidence: 52%
“…We also noted that highly efficient ablation of TGFβ occurs following topical application to 6 week old mice with another peak at 10 weeks. This timing is similar to the mouse hair anagen cycle [35]. It is possible that topical tamoxifen targeting genes in KC may have heightened efficiency during anagen.…”
Section: Discussionmentioning
confidence: 52%
“…Histological analysis (Fontana-Masson staining) of the back skin of 5-week old mice, revealed that similarly to KIT +/+ control mice, the hair follicles of both KIT Dup/+ and KIT D17/+ mice are long and the dermal papilla in the hair bulb is completely coated by the matrix, the keratogenous zone region is clearly visible and is connected to the hair shaft and dermal papilla, and fibrous tract is substantially invisible in the skin (Figure 2). These results indicate that similar to the KIT +/+ control mice, the hair follicles of 5-week-old KIT Dup/+ and KIT D17/+ mice are in the growing stage (anagen V or VI), which is advantageous for observations of hair follicle shape, and melanin distribution since melanin synthesis is more active during this stage (Hou et al, 2016). The hair follicle shape implies that both the splice mutation and CDS duplication mutation did not impair the hair follicle development significantly.…”
Section: The Kit Splice Mutation Significantly Reduces Melanin Accumumentioning
confidence: 53%
“…2). These results indicate that similar to the KIT +/+ control mice, the hair follicles of 5-week-old KIT Dup/+ and KIT D17/+ mice are in the growing stage (anagen V or VI), which is advantageous for the observation of the hair follicle shape, and melanin distribution due to melanin synthesis is more active during this stage [15]. The results of hair follicle shape imply that both the splice mutation and duplication mutation did not impair the hair follicle development significantly.…”
Section: Resultsmentioning
confidence: 86%